Answer:
30 60 90 triangle
the hypotenuse is twice the length of the shorter leg length.
Answer:
x = 486956.5217
Step-by-step explanation:
5.75% of x = 28000
Of means multiply
Change the percent to a decimal
.0575 * x = 28000
Divide by .0575 on each side
.0575/.0575 * x = 28000/.0575
x = 486956.5217
If <span>y = –4x – 7, the x-intercept is found by setting y=0 and solving for x:
</span><span>0 = –4x – 7 => 4x = -7, or x = -7/4 The x-intercept is (-7/4, 0).
</span><span>The y-intercept is found by setting x = 0 and reading off the value of y:
y = –4x – 7 => y = 0 - 7, or y = -7. The y-intercept is (0, -7).</span>
Answer:
Equilateral triangles are always acute triangles.
Scalene triangles are sometimes acute triangles.
Right triangles are never acute triangles.
Obtuse triangles are sometimes isosceles triangles.
Step-by-step explanation:
Equilateral triangles are always acute because each angle is 60⁰.
Scalene triangles have sides that are different lengths. They can be right, obtuse, or acute.
A right triangle is never acute because it has a 90⁰ angle. Acute means all angles are less than 90⁰.
An obtuse triangle can be either scalene or isosceles. It always has one angle greater than 90⁰ (obtuse).
Answer:
20-(10 2/9)-(5 1/4)= 4.52777777778 inches decimal or 163/36
Step-by-step explanation:
Simplify the following:
20 - (10 + 2/9) - (5 + 1/4)
Put 10 + 2/9 over the common denominator 9. 10 + 2/9 = (9×10)/9 + 2/9:
20 - (9×10)/9 + 2/9 - (5 + 1/4)
9×10 = 90:
20 - (90/9 + 2/9) - (5 + 1/4)
90/9 + 2/9 = (90 + 2)/9:
20 - (90 + 2)/9 - (5 + 1/4)
90 + 2 = 92:
20 - 92/9 - (5 + 1/4)
Put 5 + 1/4 over the common denominator 4. 5 + 1/4 = (4×5)/4 + 1/4:
20 - 92/9 - (4×5)/4 + 1/4
4×5 = 20:
20 - 92/9 - (20/4 + 1/4)
20/4 + 1/4 = (20 + 1)/4:
20 - 92/9 - (20 + 1)/4
20 + 1 = 21:
20 - 92/9 - 21/4
Put 20 - 92/9 - 21/4 over the common denominator 36. 20 - 92/9 - 21/4 = (36×20)/36 + (4 (-92))/36 + (9 (-21))/36:
(36×20)/36 + (4 (-92))/36 + (9 (-21))/36
| 3 | 6
× | 2 | 0
| 0 | 0
7 | 2 | 0
7 | 2 | 0:
720/36 + (4 (-92))/36 + (9 (-21))/36
4 (-92) = -368:
720/36 + (-368)/36 + (9 (-21))/36
9 (-21) = -189:
720/36 - 368/36 + (-189)/36
720/36 - 368/36 - 189/36 = (720 - 368 - 189)/36:
(720 - 368 - 189)/36
720 - 368 - 189 = 720 - (368 + 189):
(720 - (368 + 189))/36
| 1 | 1 |
| 3 | 6 | 8
+ | 1 | 8 | 9
| 5 | 5 | 7:
(720 - 557)/36
| | 11 |
| 6 | 1 | 10
| 7 | 2 | 0
- | 5 | 5 | 7
| 1 | 6 | 3:
Answer: 163/36